New labdane diterpenoids from Croton laui and their anti-inflammatory activities. Issue 19 (1st October 2016) - Yang, Li; Zhang, Yu-Bo; Chen, Li-Feng; Chen, Neng-Hua; Wu, Zhong-Nan; Jiang, Si-Qi; Jiang, Lin; Li, Guo-Qiang; Li, Yao-Lan; Wang, Guo-Cai
Graphical abstract: Abstract: Nine new labdane diterpenoids (1 –9 ) were isolated from the aerial parts of Croton laui, along with eight known analogues (10 –17 ). Their structures were identified on the basis of the spectral data (IR, UV, HRESIMS, 1D and 2D NMR), and the structure of8 was confirmed by single crystal X-ray diffraction analyses. In addition, compounds1, 4, 7, 8, and14 showed weak anti-inflammatory activities in LPS-stimulated RAW 264.7 cells.